2015
DOI: 10.1002/micr.22514
|View full text |Cite
|
Sign up to set email alerts
|

The venae comitantes clipping test for the evaluation of the venous drainage of the radial forearm free flap

Abstract: Risks of failure of the radial forearm free flap (FRFF) are mainly related to venous congestion. Two different venous drainage system have been described for the FRFF, but the choice of the best one is still controversial. The superficial systems have a larger diameter and a thicker wall veins which makes them easier to anastomose. The deep system provides most part of the venous outflow if the caliber of the venae comitantes (VCs) is adequate. We propose an intra-operative method to evaluate the FRFF venous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…There is still a debate as to which venous system (cephalic or comitantes veins) should be anastomosed, but we found the anastomosis of the cephalic vein only was reliable in 71.6 % of the cases (n = 78). This finding confirms the recent experience of S. Razzano et al [11]. Adequate venous out-flow must be assured to guarantee the survival of free flaps.…”
Section: Discussionsupporting
confidence: 91%
“…There is still a debate as to which venous system (cephalic or comitantes veins) should be anastomosed, but we found the anastomosis of the cephalic vein only was reliable in 71.6 % of the cases (n = 78). This finding confirms the recent experience of S. Razzano et al [11]. Adequate venous out-flow must be assured to guarantee the survival of free flaps.…”
Section: Discussionsupporting
confidence: 91%
“…Razzano et al ., 2016[ 12 ] in 2013 have described the ‘vena comitantes clipping test’. Here, the authors dissect the vena comitantes and the cephalic vein at the level of cubital fossa and then clips the vena comitantes to test the venous drainage sufficiency in the skin paddle of the radial forearm flap.…”
Section: Discussionmentioning
confidence: 99%
“…Venous drainage of RFFF is double, including the superficial venous system and the deep radial system with vena comitans. Razzano et al (Razzano et al, 2016) described a surgical technique to avoid venous complications: branching the superficial system alone at the level of the cephalic vein or branching the deep system alone using one or two venae comitantes. If only one system is anastomosed (Selber et al, 2011), Selber et al reported that 5.7% of postoperative congestion needs revision surgery for flap salvage in each configuration.…”
mentioning
confidence: 99%